RESTORATION OF RIAU SULTANATE-OTTOMAN RELATIONS (1857-1904):: Explanatory Factors - Alaeddin Tekin, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
During the second half of the nineteenth century there was a resurgence in relations and cooperation between the Malay Archipelago and the Ottoman Empire. Historical analysis of the policy followed by the Ottoman Caliphate in its relations with the Riau Sultanate contributes to a better understanding of the relations between the Ottoman Empire and the Malay World. The historical background of the relations between the two regions is mainly characterized by a lapse of approximately three centuries (c. 1570-1850), the reasons for which are analysed in this study. The main purpose of this study is to examine the relationship between the Ottoman State and the Sultanate of Riau through primary sources, from 1857 to 1904. The Riau Sultanate, an important polity in the Malay World, re-established its relations with the Ottoman State in 1857, and these continued until 1904, as expounded in detail in this study, based on Ottoman archives. This study extends knowledge of the neglected area of Ottoman-Malay relations with substantive new insights for contemporary cultural directions in relations between modern Turkey and the Malay World.